American spirits : the famous Fox sisters and the mysterious fad that haunted a nation - Rosenstock, Barb (Calkins Creek, 2025)
In March 1848, strange "rap" sounds were heard at the Fox family's home in Hydesville, New York. The family's daughters, Kate and Maggie, discovered they could communicate with the spirit responsible, who claimed to be a murdered traveling peddler. This event sparked a media frenzy, and the sisters, guided by their older sister Leah, became famous spirit mediums, holding public exhibitions and advising celebrities. However, questions about their legitimacy arose, especially as the demand for spiritual communication grew during the Civil War, while media campaigns against the sisters also gained momentum.